acercamiento a la conceptualización de algunas emociones en el patrimonio fraseológico del euskera y del castellano - Aznárez Mauleón, Mónica; Santazilia Salvador, Ekaitz (Huarte de San Juan. Filología y Didáctica de la Lengua, 2016)
The aim of this work is to unfold one of the lines of phraseological research that were considered interesting in the context of the Intangible Cultural Heritage Archive of Navarre Research Group (Aznárez, 2014): the comparative study, from a cognitive and ethnolinguistic point of view, of the existing expressions in Basque and Spanish. More specifically, this contribution focuses on a group of phraseological expressions –verbal locutions and collocations that describe a person’s mood or the experience of an emotion by a person– with the aim at discovering the way both languages have conceptualized this experiential field. This work is based on the theoretical principles of cognitive linguistics and phraseology (Lakoff, 1987; Lakoff y Johnson, 1980; Kövecses, 2014; Dobrovols’kij, 2007) as well as on the methodology followed in the various studies devoted to the conceptualization of emotions and feelings in different languages (Kövecses, 1995, 2000; Maalej, 2004; Iñesta y Pamies, 2002, etc.), and confirms, in line with what has been observed in the works mentioned, both the embodiment hypothesis and the existence of conceptualizations which are specific to the culture of a community.
Keywords: Cognitive phraseology; basque; spanish; emotions; embodiment